The Transformation of npr. - Dorroh, Jennifer (American Journalism Review)
This article examines how National Public Radio (NPR) is transforming itself for the 21st century. As many media outlets are having difficulties incorporating new technology such as the internet into their traditional business strategies, NPR is embracing it. They are putting their journalists, such as Lee R. Hill, through courses on multimedia journalism to facilitate using the internet as a way to enhance their reporting on the radio. Editorial Director Dick Meyer describes using podcasts, the web and mobile devices as a cultural shift.